(3JHjjf GdMbGFb aj TQM cfR GdObGFbs - (3aNQ GdOjf CHh eMeO YKeGf Hf Ydj Hf eMLf GdRjdYj, YKeGf GdRjdYj,J (B743 (3g` s ((3eMeO Hf WGgQ GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOhQ GdYGQajf HfhQ gOGjJg hRjfgG HGdEjeGf heG CdgegG ef MceJg MeO YGQa dYXeJg s
(3BNQgG (B:s
(3fLR GdLRA GdChd ef TQM GdcfRq s
(3GdcJGH GdeTQhM(B: (3cfR GdObGFb ddfSai GdeJhai (B710 (3g`s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI ceG ai BNQgG Ydi jO GdMGL jhSa Hf EHQGgje GdYWGQ (B1134 (3g`s
(3ai Chd GdfSNI agQSJ HehVhYGJ GdcJGH hJedc s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdMfajs